2022
DOI: 10.15294/kemas.v18i1.36437
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Awareness: Family Practices in Indonesian Borderland

Abstract: Poor family nutritional practice is one of the major leading causes of stunting in children aged 0-59 months. Good family nutrition practices are one of the primary keys to stunting prevention. It can also reduce the prevalence of stunting and the impact it has on families, which are included in the category of stunting risk families. This study aimed to investigate nutrition-aware family practices at Haliwen Health Center, Atambua-one of the border areas of the Republic of Indonesia (RI) and Democratic Republ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The results showed that most mothers gave exclusive breastfeeding to infants aged 0-6 months. Exclusive breastfeeding means the baby gets only breast milk without any additional food (except medicines, vitamins and minerals) until six months (Binns et al, 2020;Hadi et al, 2022;Nahak et al, 2022). Breast milk is the primary source of food for newborns up to 6 months of age (Ahmad et al, 2015;Beal et al, 2018;Gannon et al, 2020).…”
Section: Based On Tablementioning
confidence: 99%
See 3 more Smart Citations
“…The results showed that most mothers gave exclusive breastfeeding to infants aged 0-6 months. Exclusive breastfeeding means the baby gets only breast milk without any additional food (except medicines, vitamins and minerals) until six months (Binns et al, 2020;Hadi et al, 2022;Nahak et al, 2022). Breast milk is the primary source of food for newborns up to 6 months of age (Ahmad et al, 2015;Beal et al, 2018;Gannon et al, 2020).…”
Section: Based On Tablementioning
confidence: 99%
“…Breast milk contains carbohydrates, water, fat, protein and essential nutrients that contribute to the growth and development of toddlers (Ahmad et al, 2015). Exclusive breastfeeding has been proven to reduce the risk of stunting effectively (Hijra et al, 2016;Badriyah and Syafiq, 2017;Uwiringiyimana et al, 2019;Binns et al, 2020;Nur et al, 2021;Hadi et al, 2022;Nahak et al, 2022). It is because breast milk contains nutrients for physical development and antibodies, thereby reducing morbidity and the incidence of infection in infants.…”
Section: Based On Tablementioning
confidence: 99%
See 2 more Smart Citations
“…Nutrition-aware families have five indicators: weighing regularly, breastfeeding exclusively, consuming diverse foods (balanced nutrition), consuming iodized salt, and taking supplements as recommended (UGM, 2019). Five indicators of Nutrition-aware behavior from the results of the study have been shown to contribute to the incidence of stunting in children (Lindawati et al, 2023;Rosalina et al, 2023;Berawi et al, 2022;Nahak et al, 2022;Fitriah et al, 2021). Another study shows that there is a contribution to Nutrition-aware family indicators, namely weight weighing in Posyandu (Prasetyani et al, 2023), exclusive breastfeeding (Lindawati et al, 2023;Hadi et al, 2022), feeding practices (Quamme &;Iversen, 20220;Gunawan et al, 2022), iodized salt consumption (Abbag et al, 2021;Gunawan et al, 2022), Fe and vitamin A supplements (Silaban et al, 2022), against the incidence of stunting in children.…”
Section: Introductionmentioning
confidence: 95%